Mathematical Modeling of Thermal Regime in the Launch Vehicle Fairing at the Stage of Prelaunch Preparation - Kozachyna, V. A.; Biliaiev, M. M.; Biliaieva, V. V.; Semenenko, P. V.; Yakubovska, Z. M. (Science and Transport Progress, 2025)
Purpose. The development of satellite communication systems is based on the transportation of satellites in space. The satellite is transported into orbit by a launch vehicle. The satellite is placed in the transportation compartment in the middle of the main fairing. At the pre-launch stage, it is necessary to comply with the harsh environmental conditions inside the main fairing. In particular, it is very important to predict the temperature field in the transport compartment inside the main fairing during its forced ventilation at the pre-launch stage. To solve this problem, it is necessary to have specialized mathematical models. The main goal of this work is to develop a fast-calculating model for estimating the temperature fields inside the launch vehicle fairing. Methodology. The energy equation was used to calculate the temperature field formed by the ventilation of the transport compartment and the heat generated by various elements of the satellite. This equation took into account the intensity of heat emission from different parts of the satellite, the pattern of airflow around the satellite, and heat transfer in the transportation compartment. The inhomogeneous airflow velocity field in the cargo compartment was calculated based on a potential flow model. Finite-difference schemes are used for numerical integration of the model equations. Findings. A computer code has been developed that implements the proposed numerical model. The results of computational experiments to assess the temperature regime in the main fairing of the launch vehicle for different satellites are presented. Originality. A fast-calculating CFD model for analyzing thermal fields in the middle of the launch vehicle fairing at the stage of prelaunch preparation has been created. The model makes it possible to determine the zones with sub- and over-temperature in the middle of the fairing. Practical value. The developed numerical model can be useful for selecting and justifying the ventilation mode of the main fairing of the launch vehicle at the pre-launch stage in order to ensure the recommended temperature range near the satellite. It can also be used for the initial assessment of the temperature in the main fairing at the stage of justifying the thermal control mode for a particular satellite or satellite system.